Inhaled ciclesonide does not affect production of antibodies or elimination of virus in patients with COVID-19: Subanalysis of a multicenter, open-label randomized trial - Ishizaka, Yukihito; Terada-Hirashima, Junko; Sadamasu, Kenji; Hojo, Masayuki; Suzuki, Manabu; Matsunaga, Akihiro; Nagashima, Mami; Izumi, Shinyu; Takasaki, Jin; Miyoshi-Akiyama, Tohru; Sugiyama, Haruhito (Drug Discoveries & Therapeutics, 2023)
During an earlier multicenter, open-label, randomized controlled trial designed to evaluate the effectiveness of high-dose inhaled ciclesonide in patients with asymptomatic or mild coronavirus disease 2019 (COVID-19), we observed that worsening of shadows on CT without worsening of clinical symptoms was more common with ciclesonide. The present study sought to determine if an association exists between worsening CT shadows and impaired antibody production in patients treated with inhaled ciclesonide. Eighty-nine of the 90 patients in the original study were prospectively enrolled. After exclusions, there were 36 patients each in the ciclesonide and control groups. We analyzed antibody titers against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleocapsid protein at various time points. Changes in viral load during treatment were compared. There was no significant difference in age, sex, body mass index, background clinical characteristics, or symptoms between the two groups. Although evaluation on day 8 suggested a greater tendency for worsening shadows on CT in the ciclesonide group (p = 0.072), there was no significant difference between them in the ability to produce antibodies (p = 0.379) or the maximum antibody titer during the clinical course. In both groups, worsening CT shadows and higher viral loads were observed on days 1-8, suggesting ciclesonide does not affect clearance of the virus (p = 0.134). High-dose inhaled ciclesonide did not impair production of antibodies against SARS-CoV-2 or affect elimination of the virus, suggesting that this treatment can be used safely in patients with COVID-19 patients who use inhaled steroids for asthma and other diseases.